Integrated Fuzzy AHP and Weighted-Fuzzy Goal Programming Approach to Solve Supplier Selection Problem with Subjective Factors - Annas S. Setiyoko; Udisubakti Ciptomulyono; I. K. Gunarta (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2007)
Fuzzy goal programming (FGP) method used in supplier selection process shows that decision maker preferences on each fuzzy goal are not yet considered. In order to accommodate those preferences, that are stated as weight on each fuzzy goal, and called weighted fuzzy goal programming (WFGP) method. Then, the developed method is utilized to solve international supplier selection problem. There would be 4 objective functions developed i.e. to minimize net cost, to minimize late delivery, to minimize net rejected material, as well as to maximize business relationship. Maximization of business relationship objective function is intended to obtain right suppliers related to it score. Those objective functions are optimized subject to total demand, maximum supplier capacity, total purchasing cost based on owner estimate, and minimum order requested by suppliers. Linguistic variables are used to measure criterions in business relationship factor. To do so, fuzzy analytic hierarchy process (FAHP) transforms that qualitative manner in linguistic variables to numerical number as a constant in business relationship objective function. Those proposed method provides enhanced solution that represent decision maker preferences than FGP. That is exhibited with equal relationship between weighted goals value and the output of those weighted goals.